Symphosius the Aenigmata : An Introduction, Text and Commentary - Leary, T. J. (Criminal Practice Ser, 2014)
Cover -- Half-title -- Title -- Copyright -- Contents -- Preface and Acknowledgements -- List of Tables -- Select Bibliography -- Introduction -- 1 Author and title -- 2 Date -- 3 The collection -- (a) Martial, Symphosius, Riddles and the Saturnalia -- (b) Order and arrangement -- (c) Literary style -- (d) Latinity and metre -- (e) Literary debts -- 4 Nachleben -- 5 The text -- (a) Sigla -- (b) Differences with Shackleton Bailey's 1982 Teubner text -- Latin Text -- Commentary -- 1 A stylus -- 2 A reed pen -- 3 A ring with a jewel-stone -- 4 A key -- 5 A chain -- 6 A tile -- 7 Smoke -- 8 Cloud -- 9 Rain -- 10 Ice -- 11 Snow -- 12 A river and a fish -- 13 A ship -- 14 A chick in an egg -- 15 A viper -- 16 A bookworm -- 17 A spider -- 18 A snail -- 19 A frog -- 20 A tortoise -- 21 A mole -- 22 An ant -- 23 A fly -- 24 A weevil -- 25 A mouse -- 26 A crane -- 27 A crow -- 28 A bat -- 29(31) Phoenix -- 30(29) A hedgehog -- 31(30) A louse -- 32 A bull -- 33 A wolf -- 34 A fox -- 35 A nanny goat -- 36 A pig -- 37 A mule -- 38 A tiger -- 39 A centaur -- 40 A poppy -- 41 A mallow -- 42 A beet -- 43 A gourd -- 44 An onion -- 45 A rose -- 46 A violet -- 47 Incense -- 48 Myrrh -- 49 Ivory -- 50 Hay -- 51 A mill -- 52 Flour -- 53 A vine -- 54 A hook -- 55 A needle -- 56 A boot -- 57 A hobnail -- 58 A hair -- 59 A ball -- 60 A saw -- 61 An anchor -- 62 A bridge -- 63 A sponge -- 64 A trident -- 65 An arrow -- 66 A whip -- 67 A lantern -- 68 A window pane15 -- 69 A mirror16 -- 70 A water-clock -- 71 A well -- 72 A pipe -- 73 Bellows -- 74 A stone -- 75 Lime -- 76 Flint -- 77 Wheels -- 78 A ladder -- 79 A besom -- 80 A bell -- 81 A flask -- 82 Seasoned wine -- 83 Wine turned to vinegar -- 84 An apple -- 85 A ham -- 86 A hammer -- 87 A pestle -- 88 A bronze strigil -- 89 A bathhouse -- 90 A die -- 91 Money -- 92 A woman who has given birth to twins.